Concepções de gênero e sexualidade no curso de pedagogia UFMA/Codó: criando espirais de conhecimento com o olhar discente - SIMÕES, Simone Cristina Silva (2020)
This study presents a mapping of gender and sexuality theories in the undergraduate teaching course offered by the Federal University of Maranhao (UFMA) in Codó. It is based on the theories of Deleuze and Guatarri. The objective is to analyze the application of gender and sexuality theories in the teaching course of the University of Maranhao in Codó, Campus VII, from 2015 to 2019. The study presents possible contributions of gender and sexuality theories to the alumni from Cocais region of Maranhao State in Brazil. Therefore, this study is aligned to post-critical theories and it is inspired by decolonial works to: 1) Identify the policies of gender and sexuality at the teaching faculty handbook of the College of Education of the UFMA, Campus VII in Codó, Maranhao State, after the curricular guidelines from the year of 2018; 2) Identify the elements of gender and sexuality theories presented in the final papers written by the class in 2019; 3) Analyse the ideas of gender and sexuality at the papers made by the alumni of the class of 2015 through an activity called educational masterclass; 4) To acknowledge the contributions from the gender theories, and possible misunderstandings generated by their absence in teachers; undergrad studies, and their professional actions in the elementary schools. The methodology used was: documental analysis of the handbook of the College of Education in Codó and students’ papers; the use of Bardin and Gauthier theories to mapping the papers written in an educational masterclass conducted with the students. Therefore, this study contributes to the elementary school teaching and learning courses with new perspectives and comprehensive dialogues on gender and sexuality theories in their colleges or universities.